LEADERSHIP CHARACTERISTICS IN A DEVELOPING WORLDPEDAGOGICAL-PSYCHOLOGICAL FACTORS OF DEVELOPMENT (Universal International Scientific Journal, 2026)
This article analyzes the transformation of leadership characteristics in the era of globalization and intensive information exchange. It is argued that a modern leader should have not only management skills, but also a high level of information culture and adaptability. The article reveals the pedagogical (educational content, methodology) and psychological (emotional intelligence, stress resistance, creativity) factors of forming a leader's personality. Also, scientific conclusions are presented on the impact of digital literacy on leadership effectiveness in an information society
Keywords: informational world; leadership; pedagogical factors